Near- and Offshore Macrofauna Communities and Their Physical Environment in a South-Eastern North Sea Sandy Beach System - Kröncke, Ingrid; Becker, Lydia R.; Badewien, Thomas H.; Bartholomä, Alexander; Schulz, Anne-Christin; Zielinski, Oliver (Frontiers in Marine Science, 2018)
The aim of the study is to compare spatial variation of macrofauna communities in the near- and offshore zone of the beach system of the island of Spiekeroog (German North Sea) in order to environmental parameters such as hydrodynamics and sediment type. The analysis of hydroacoustic backscatter signals have been used to classify the sea bottom characteristics in terms of surface roughness. Sampling was carried out in May 2014. Samples were taken along a 3.4 km transect in north-south direction. The analyses of the spatial distribution structure of the environmental parameters and the macrofauna communities revealed a clear zonation of the transect line into an inner, outer nearshore, and offshore zone. The inner nearshore was exposed to high hydrodynamic energy with a high variability in sediment composition, a lack of biogenic structures, lowest taxa numbers, but a considerably high diversity (Shannon Wiener index). The hydrodynamic conditions in the nearshore zone were more stable. Sediment distribution was homogenous. Taxa number and abundances increased and polychaete species such as Magelona johnstonii, Spiophanes bombyx, and Lanice conchilega characterized the community. In the offshore zone, taxa number and abundances increased even further. Lanice conchilega dominated the community. While current velocities of the bottom layers decreased, mud contents slightly increased.